1995
DOI: 10.1007/bf00216783
|View full text |Cite
|
Sign up to set email alerts
|

Superantigens and pseudosuperantigens of gram-positive cocci

Abstract: Superantigens use an elaborate and unique mechanism of T lymphocyte stimulation. Prototype superantigen are the pyrogenic exotoxins produced by Staphylococcus aureus and Streptococcus pyogenes. Many candidate proteins of bacterial, viral and protozoal origin have recently been reported to be superantigens. In most cases the evidence that these proteins are in fact superantigens is highly indirect. In this review the evidence that gram-positive cocci produce superantigens other than the pyrogenic exotoxins is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 83 publications
2
27
0
Order By: Relevance
“…One of the major concerns regarding SEB in aerosol form is its ability to produce severe lung damage. Enterotoxin-producing S. aureus strains are associated with toxic shock syndrome, which includes systemic and respiratory complications such as cardiomyopathy, renal failure, electrolyte imbalances, disseminated intravascular coagulation, encephalopathy, and adult respiratory distress syndrome (2,13,18,25,31). Since in past studies SEB aerosol exposure was shown to induce lethal pulmonary lesions in nonhuman primates, we sought to examine whether aerosol delivery of SEB to the HLA-DQ8 mice induced respiratory damage (35,39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major concerns regarding SEB in aerosol form is its ability to produce severe lung damage. Enterotoxin-producing S. aureus strains are associated with toxic shock syndrome, which includes systemic and respiratory complications such as cardiomyopathy, renal failure, electrolyte imbalances, disseminated intravascular coagulation, encephalopathy, and adult respiratory distress syndrome (2,13,18,25,31). Since in past studies SEB aerosol exposure was shown to induce lethal pulmonary lesions in nonhuman primates, we sought to examine whether aerosol delivery of SEB to the HLA-DQ8 mice induced respiratory damage (35,39).…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus and group A streptococci are responsible for a wide range of mild to life-threatening infections, including scarlet fever, pharyngitis, dermatitis, infectious arthritis, and toxic shock syndrome (2,13,18,25,31). These pathogenic bacteria use several virulence mechanisms to enhance their toxicity after infection, including the M protein, diffusible enzymes (e.g., DNase), and streptolysin.…”
mentioning
confidence: 99%
“…It is the immune system and not LPS that kills the host. There are many other microbial pathogens that are able to activate the immune system nonspecifically, which is often referred to as “polyclonal lymphocyte activation.”79 Some of these products are known in immunology as “superantigens.”80–82 The immunobiology of superantigens is complex and is beyond the scope of this paper. However, many of them are pyrogenic substances, 83 and therefore capable of activating APR.…”
Section: Host Defense In Febrile Illnessmentioning
confidence: 99%
“…Streptococcal pyrogenic exotoxins have been shown to act as superantigens that activate T lymphocytes expressing certain T cell receptor V β regions [1]. These may include potentially autoreactive T cells and superantigens have therefore been implicated in the aetiology of autoimmune diseases [2].…”
Section: Introductionmentioning
confidence: 99%